The Concept of Sufism by Al-Muhasibi and Al-Ghazali (Intertextuality Studies of Al-Washaya and Al-Munqidz min Al-Dhalal) - Miftahul ula (UIN K.H. Abdurrahman Wahid Pekalongan, 2022)
This study aims to reveal the concept of Sufism of al-Muhasibi and al-Ghazali in the autobiography of Kitab al-Washaya and al-Munqidz min al-Dhalal as well as the intertextuality of the autobiography of al-Washaya and al-Munqidz min al-Dhalal?. The primary sources used are al-Washaya by al-Muhasibi and al-Munqidz min al-Dhalal by al-Ghazali. The science of Sufism for al-Muhasibi and al-Ghazali is the scientific culmination of various epistemologies whose truth validity can be justified. For both, Sufism is able to satisfy intellectual and spiritual thirst. The intertextual relationship between the two works of Sufism can be seen in the background of the two authors in the form of the cultural background, intellectual and psychological conditions of the two figures before their conversion to Sufism. Intertextual relations are also found in themes, plots, characterizations and language styles.